In vivo tibiofemoral skeletal kinematics and cartilage contact arthrokinematics during decline walking after isolated meniscectomy. (January 2018) - Zheng, Liying; Carey, Robert; Thorhauer, Eric; Tashman, Scott; Harner, Christopher; Zhang, Xudong
Highlights: In vivo cartilage contact arthrokinematics are examined noninvasively, comparing the meniscectomized to the contralateral intact knees. Isolated meniscectomy effects are assessed without other confounding injuries. Cartilage-based arthrokinematics is more sensitive than skeletal kinematics. Abstract: We investigated the effects of isolated meniscectomy on tibiofemoral skeletal kinematics and cartilage contact arthrokinematics in vivo . We recruited nine patients who had undergone isolated medial or lateral meniscectomy, and used a dynamic stereo-radiography (DSX) system to image the patients' knee motion during decline walking. A volumetric model-based tracking process determined 3D tibiofemoral kinematics from the recorded DSX images. Cartilage contact arthrokinematics was derived from the intersection between tibial and femoral cartilage models co-registered to the bones. The kinematics and arthrokinematics were analyzed for early stance and loading response phase (30% of a gait cycle), comparing the affected and intact knees. Results showed that four patients with medial meniscectomy had significantly greater contact centroid excursions in the meniscectomized medial compartments while five patients with lateral meniscectomy had significantly greater cartilage contact area and lateral shift of contact centroid path in the meniscectomized lateral compartments, comparing to those of the same compartments in the contralateral intact knees. No consistent difference however was identified in the skeletal kinematics. The current study demonstrated that cartilage-based intra-articular arthrokinematics is more sensitive and insightful than the skeletal kinematics in assessing the meniscectomy effects.